Morality and the Nature of Politics - Čelutka, Simas (Politologija, 2019)
The aim of the paper is to reconstruct and analyze Alvydas Jokubaitis’s understanding of politics. It is argued that Jokubaitis couples politics with morality in opposition to the liberal project of the autonomy of politics, which seeks to separate these two fields of human activity. According to Jokubaitis, politics is a realm of realization of the spiritual side of human nature. That is the reason why, through morality, he also tries to align politics with other domains of human spirituality, such as religion and metaphysics. What is common to politics, morality, religion, and metaphysics is the sphere of normativity, i.e., that of purposes, principles, and imperatives. At the same time, Jokubaitis attacks those schools of modern thought which interpret politics as corresponding solely to the physical, animal side of human nature. In this regard, positivism and scientism are singled out as the crudest attempts to misconstrue the nature of politics. The paper is based on a conviction that the acknowledgement of the importance of morality allows one to piece together Jokubaitis’s various considerations about the nature and distinctiveness of politics into a coherent whole.
Keywords: politics; morality; autonomy of politics; Jokubaitis; Schmitt